RESPONSES OF GIVEN THE WATER HYACINTH (Eichornniacrassipes) ONTHE TONDANO WATERSHED SEDIMENT TOWARD THE GROWTH OF CORN CROP ((Zea mays sp.) - Alberthina Y. Frasawi; Meldi T.M Sinolungan; Wiesje J.N Kumolontang (Universitas Sam Ratulangi, 2018)
AbstractTondano River is an outlet of Tondano Lake played important roles in the life society of North Sulawesi Province. More increase the population growth, more increase the needed of people to that river, so that more increase the problems, such as sedimentation process occurred as the waste/erosion discharge existed at the Tondano estuary. The problemis the processes of sediment discharge could be used as media for planting and the water hyacinth as compost. The objective of this research was to know the responses of given the water hyacinth compost on the sediments of Tondano Watershed with indicator of corn crop (Zea mays sp.) on the field. Methods were used Randomized Block Design, consisted of some treatments, i.e.: ST0 as control, ST1 – compost of 10 t/ha, ST2 – compost of 20 t/ha, ST3 – compost of 30 t/ha, in three groups as for 12 experimental plots. Results showed that, given the water hyacinth compost on the sediments of Tondano River gave the significant effect for corn growth, that is, the treatment of 30 t/ha. Keywords: sediment, water hyacinth, compost, TondanoWater shed.